Revolutions as rhetorical movements: a movement study of the Egyptian Arab Spring Revolution - Johnson, Jordan (Kansas State University, 2015)
The 2011 Arab Spring Revolutions across the Middle East North Africa (MENA) region drew international attention to the collection action phenomenon of revolutions. Despite having a significant impact on today’s globalized world, revolutions have been widely unexplored by social movement rhetorical scholars. This lack of study has prompted scholars to call for the investigation of the role human agency plays during revolutions (Morris, 2000). Rhetorical scholars are well-suited to meet this call but lack a methodological framework to examine revolutions. In responding to Morris’ call and with an interest in adding to the body of rhetorical social movement literature, this thesis asks two research questions. What are the rhetorical characteristics of revolutions? Are revolutions rhetorically distinct from social movements? To answer these questions, this thesis translates Jack Goldstone’s (1998) Divergent View of Social Movements and Revolutions into a rhetorical model for studying revolutions. This adaptation of the political science model relies heavily on Leland Griffin’s (1969) and Charles Stewart’s (1980) models of social movements. Additionally, the adapted model also incorporates James Wilkinson’s (1989) discussion of revolutionary rhetorical functions. The application of the new rhetorical model to the Egyptian Arab Spring reveals revolutions rhetorically develop and function in ways that creates a clear distinction between revolutions from social movements. These findings prompt discussion of methodological and critical implications.
Keywords: Revolutions; Social movements; Rhetorical analysis; Arab Spring; Egypt; Communication (0459)